Construction of root tip density function and root water uptake characteristics in alpine meadows - Deng, Bin; Weng, Baisha; Yan, Denghua; Xiao, Shangbin; Fang, Haotian; Li, Meng; Wang, Hao (Frontiers in Plant Science, 2022)
Accurate calculation of root water uptake (RWU) is the key to improving vegetation water use efficiency and identifying water cycle evolution patterns, and root tips play an important role in RWU. However, most of the current RWU model in the alpine meadow is calculated based on the root length density (RLD) function. In this study, a large number of roots, soil hydraulic conductivity, and physicochemical property indices were obtained by continuous field prototype observation experiments for up to two years. It was found that the RLD and root tip density (RTD) in alpine meadows decrease by 16.2% and 14.6%, respectively, in the wilting stage compared to the regreening stage. The RTD distribution function of the alpine meadow was constructed and the RWU model was established accordingly. The results show that the RTD function is more accurate than the RLD function to reflect the RWU pattern. Compared with RLD, the simulated RWU model constructed by using RTD as the root index that can effectively absorb water increased by 24.64% on average, and the simulated values were more consistent with the actual situation. It can be seen that there is an underestimation of RWU calculated based on the RLD function, which leads to an underestimation of the effect of climate warming on evapotranspiration. The simulation results of the RWU model based on RTD showed that the RWU rate in the regreening stage increased by 30.24% on average compared with that in the wilting stage. Meanwhile, the top 67% of the rhizosphere was responsible for 86.76% of the total RWU on average. This study contributes to the understanding of the alpine meadow water cycle system and provides theoretical support for the implementation of alpine meadow vegetation protection and restoration projects.